2011
DOI: 10.1007/s00268-011-1200-x
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Fracture of Intravenous Ports and its Management

Abstract: Most catheter fractures were caused by material weakness. If catheter fracture is confirmed, further intervention for port and catheter removal is recommended. Female gender, intravenous port implantation via the subclavian route, and the Arrow Fr. 8.1 port were found to be risk factors. Patients with these risk factors should be monitored closely to avoid catheter fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 22 publications
1
40
0
Order By: Relevance
“…[1] Invasive catheter placement can impose certain risks and clinical management problems. Femoral artery is cannulated by various catheters varying in texture, length and caliber with or without guidewire assistance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1] Invasive catheter placement can impose certain risks and clinical management problems. Femoral artery is cannulated by various catheters varying in texture, length and caliber with or without guidewire assistance.…”
Section: Discussionmentioning
confidence: 99%
“…[13] It is commonly reported with subclavian approach and postulated to be preceded by the pinch-off sign. [4] The complication could not be eliminated with internal jugular approach as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term stress, neck movement, and compression by backpacks and necklaces are considered potential causes of TIVAP catheter fracture 2. It is reported that placing a TIVAP catheter in the internal jugular vein has fewer complications than placing it in the subclavian vein 3. However, other studies have reported no difference in the frequency of complications between placing a TIVAP catheter in the internal jugular vein and that in the subclavian vein 4.…”
Section: Discussionmentioning
confidence: 99%